Experimental study on the critical breakup condition of a static armour layer. (9th December 2020) - Wang, Qiang; Wang, Lu; Wang, Tao; Yang, Kejun; Nie, Ruihua
Abstract: High‐flow intensity over a well‐developed static armour layer will significantly reduce the stability of a riverbed. However, the intensity at which the static armour layer would completely break is not known. In this study, laboratory flume experiments were conducted to analyze the response of the static armour layer to high‐flow intensity. The static armour layer was developed under the condition of steady flow with no supply of sediments. The flow intensity was increased by increasing the flow discharge, and the bed‐load rate was determined to evaluate whether the static armour layer broke. The observations indicate that when the bed shear stress is low (<1.2 times the initial bed shear stress of the pre‐armoured bed), the bed‐load transport rate is low and the mobility of the static armour layer is constrained. However, when the bed shear stress increases to 1.2 times the initial bed shear stress, the bed‐load transport rate increases, and the mobility is significantly promoted, indicating that the layer is broken. In our experiments, the characteristic particle sizes of the bed, D 50 and D 84, changed slightly before the static armour layer was broken, which signified that the composition of the riverbed slightly changed. However, the effect of the bed structure gradually increases with the increase in the flow intensity, leading to a 20% increase in the stability threshold of the static armour layer. In addition, the time to re‐form the new static armour layer after the destruction of the old one was observed to be positively correlated with flow intensity. However, further research must be conducted on the threshold of the damage of the static armour layer.